An experimental study and modeling on gas metal arc welded lap joint of A7075-T651 aluminium alloy to AZ31B magnesium alloy - M. Rafiqul, Islam (2015)
Innovative welding technique for joining aluminum and magnesium alloys in automobile, aviation, aerospace and marine industries would achieve weight reduction, high specific strength as well as increase fuel efficiency and reduce environmental pollution. However, poor mechanical properties of welding joint between aluminum and magnesium alloys due to the formation of AlmMgn type brittle intermetallic compounds is the main barrier for extensive uses of these two alloys especially in transportation sectors. No exact solution has been established yet for reliable joining while; modeling study in this area is still much lagging. This research work was carried out to conduct experimental study and mathematical modeling of mechanical properties for A7075- T651 aluminum and AZ31B magnesium alloys joints welded by gas metal arc lap welding method. Unconventional ER308L-Si stainless steel and conventional ER5356 aluminum wires were used as filler. Shielding gas used was 98% argon and 2% oxygen. The shielding gas flow rate, tip to work distance, welding current and voltage were the variable parameters. Box-Behnken technique in response surface methodology was used for design of experiments. The welding torch angle, filler wire diameter and parent metal thickness were kept constant. The ultimate tensile strength and fracture toughness of the joints were evaluated. The fracture toughness of the welding joints was calculated from yield strength and absorbed charpy impact energy of the joints using Rolfe-Novak-Barsom correlation. Mathematical models were developed based on regression analysis to relate the responses (ultimate tensile strength and fracture toughness) with welding variable parameters and validation experiments were conducted to verify the models. The significance and effects of variable parameters on the responses were also analyzed. The macro and microstructures at the welding cross section were investigated by optical microscope. The fracture surface morphologies and elements analysis at the welding cross section were carried out by scanning electron microscopy and electron dispersive X-ray spectroscopy. The results revealed that more significant mechanical properties were achieved with stainless steel filler compared to aluminum filler. The maximum yield strength, ultimate tensile strength and fracture toughness were 203.09 MPa, 249.33 MPa and 27.49 MPa√m respectively with steel filler; and 176.30 MPa, 226.28 MPa and 20.22 MPa√m respectively with aluminum filler. The analysis of variance showed that a very good fitting and variation with data, high accuracy in predicting the responses have been illustrated by the models for both fillers. The validation tests revealed that the ultimate tensile strength models can predict the responses within 0.21% and 1.81% maximum error, and fracture toughness models can predict the responses within 0.51% and 3.36% maximum error respectively. Most of the joints failed at AZ31B alloy (with steel filler) and ER5356 aluminum nugget (with aluminum filler). The investigation revealed that fracture occurred due to brittle fracture mechanism by formation of micro pores, voids, cracks, MgnOm oxides, very little amount of MgnFem and AlmMgn intermetallic compounds at AZ31B alloy, and due to micro pores, voids, cracks, AlmOn and MgmOn oxides and a good amount of AlmMgn intermetallic compounds at aluminum nugget. There was no evidence of fracture from metallurgical bonding between steel or aluminum nuggets and parent alloy. The output of this research exhibited very significant mechanical properties of the joint that can facilitate the extensive uses of A7075-T651 and AZ31B alloys in mass production of light weight vehicle structures in transportation industries